The role of insurance to protect the right of passengers in air transport in case of damage to health, injury or disposal of passengers (Vallis Aurea, 2019)
The paper deals with how carriers in air transportation sector are to deal with their liability in systematic manner, with an emphasis on passengers rights. National, international, and European Union regulations are scrutinized concerning the obligations and responsibilities of the carriers arising from a contract for carrying of persons (passengers), in the adverse event of damage to health, injury, and/or death. Furthermore, what options are available to the passengers in seeking monetary compensation regarding both property, and non-property damages. The stress is on insurance against liability which may arise from referenced contract, and also the benefits of institute of compulsory as well as voluntary insurance policy.This particular topic is very interesting, due to so-called travel law can be specified as a sub-branch of transportation, and/or respectively transport. Therefore, the sources of legal rights of so-called passenger’s rights are based on three-dimensional level, in terms of applying and comparing the legal sources on national, international, and European level.